Navigating Business Model Innovation in Chinese Manufacturing: Insights and Implications - Zhang, Yao; Mohi Ud Din, Qaiser; Yuan, Yuan (Engineering, Technology & Applied Science Research, 2024)
Despite an increasing number of manufacturing companies innovating their business models in the digital economy, how innovative business models are formed has remained an under-researched area, especially in the manufacturing industry. This study addresses the particular research gap by analyzing the business model innovation process and identifies and explores five conditions that influence the business model innovation process: creative ideas, value proposition optimization, transaction structure reconstruction, profit model exploration, and dynamic potential accumulation. Then, based on the data of 238 respondents in Chinese manufacturing companies, the fuzzy-set approach is employed by conducting Qualitative Comparative Analysis (fsQCA) to explore the configurations of the innovative business model formation process. The results show that high levels of business model innovation can be achieved through different configurations: (1) creative ideas, value proposition optimization, and transaction structure reconstruction combined with dynamic potential accumulation, (2) creative ideas, value proposition optimization, and profit model exploration combined with dynamic potential accumulation, (3) value proposition optimization, and profit model exploration combined with transaction structure reconstruction, and (4) transaction structure reconstruction combined with dynamic potential accumulation. This study contributes to the theoretical literature on business model innovation and provides practical information for manufacturing companies looking to innovate their business models.